2021
DOI: 10.1007/s40120-021-00251-6
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Comparative Bioavailability of Apomorphine Sublingual Film and Subcutaneous Apomorphine Formulations in Patients with Parkinson’s Disease and “OFF” Episodes: Results of a Randomized, Three-Way Crossover, Open-Label Study

Abstract: Introduction: In a pivotal study, apomorphine sublingual film (APL; KYNMOBI Ò ) was an effective and generally well-tolerated ondemand treatment of ''OFF'' episodes in patients with Parkinson's disease (PD), approved across the dose range of 10-30 mg. Pharmacokinetics and comparative bioavailability of APL and two subcutaneous (SC) apomorphine formulations (SC-APO [APOKYN Ò ] and SC-APO-GO [APO-go Ò PEN]) were evaluated in a randomized, threeway crossover, open-label study (NCT03292016). Methods: Patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
24
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 22 publications
7
24
2
Order By: Relevance
“…18 Importantly in the current study, QT prolongation was not observed at apomorphine C max , despite administration of apomorphine sublingual film doses exceeding those needed to achieve FULL "ON," perhaps owing to the slower rate of absorption of sublingual versus subcutaneous apomorphine. 18 There was a nonlinear relationship between C max and dose, likely due to high interpatient variability. This relationship may have also been influenced by route of administration, which requires adequate moisture in the oral cavity to facilitate dissolution of the sublingual film.…”
Section: Discussioncontrasting
confidence: 49%
See 3 more Smart Citations
“…18 Importantly in the current study, QT prolongation was not observed at apomorphine C max , despite administration of apomorphine sublingual film doses exceeding those needed to achieve FULL "ON," perhaps owing to the slower rate of absorption of sublingual versus subcutaneous apomorphine. 18 There was a nonlinear relationship between C max and dose, likely due to high interpatient variability. This relationship may have also been influenced by route of administration, which requires adequate moisture in the oral cavity to facilitate dissolution of the sublingual film.…”
Section: Discussioncontrasting
confidence: 49%
“…In a pharmacokinetic comparative bioavailability study, apomorphine sublingual film had a lower C max compared with subcutaneous apomorphine formulations at similar exposures 18 . Importantly in the current study, QT prolongation was not observed at apomorphine C max , despite administration of apomorphine sublingual film doses exceeding those needed to achieve FULL “ON,” perhaps owing to the slower rate of absorption of sublingual versus subcutaneous apomorphine 18 . There was a nonlinear relationship between C max and dose, likely due to high interpatient variability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There have been attempts to develop alternate modes of administration, but to date, all have failed primarily due to subcutaneous tissue side effects. APL-130277 is a new formulation of apomorphine that consists of a sublingual, bilayer film formulation, first registered in Canada in 2020 and FDA approved as treatment for unpredictable OFF episodes [ 96 , 97 ]. A 12-week, Phase 3, DBRCT involving patients with OFF episodes despite stable anti-PD treatment evaluated sublingual apomorphine (dose range of 10–30 mg) and reported significantly greater self-rated full ON response within 30 min versus placebo, corroborated by a nominally significant full ON response using home-dosing diaries.…”
Section: Motor Fluctuationsmentioning
confidence: 99%